STUDENTS' PERCEPTION OF THE SOCIAL COMPETENCE OF ENGLISH TEACHER - Surentu, Nada Indah; Talib, Ahmad; G, Hasriani (JTechLP: Journal of Technology in Language Pedagogy, 2024)
This research aims to determine students' perceptions of social competence in English teachers. This research is qualitative research that uses a descriptive qualitative method. The instrument used in this research is the interview. Interviews were conducted with six students who were selected using a purposive sampling technique. The results showed that English teachers who teach at SMP Negeri 1 Makale Utara, especially those who teach in grade eight, have fulfilled five indicators of social competence, namely: being inclusive and acting objectively, non-discriminatory, and communicative with fellow teachers, education personnel, parents/guardians, and the community.